Revolutionizing the AI-digital landscape a guide to sustainable emerging technologies for marketing professionals - Khang, Alex; Dutta, Pushan Kumar 1985-; Gupta, Sachin; Aayedee, Nishu; Chatterjee, Sandeep (Routledge, 2024)
« This book investigates the growing influence of artificial intelligence in the marketing sphere, providing insights into how AI can be harnessed for developing more effective and efficient marketing strategies. In addition, the book will also offer a comprehensive overview of the various digital marketing tools available to entrepreneurs, discussing their features, benefits, and potential drawbacks. This will help entrepreneurs make well-informed decisions when selecting the tools most suited to their needs and objectives. It is designed to help entrepreneurs develop and implement successful strategies, leveraging the latest tools and technologies to achieve their business goals. As the digital landscape continues to evolve rapidly, this book aims to serve as a valuable resource for entrepreneurs looking to stay ahead of the curve and capitalize on new opportunities. The book's scope encompasses a wide range of topics, including customer experience, content marketing, AI strategy, and digital marketing tools. »--Quatrième de couverture
A Productivity press book
Keywords: Marketing / Data processing; Artificial intelligence; Marketing / Informatique; Intelligence artificielle; artificial intelligence; Aufsatzsammlung